Determinants of Non-Performing Financing in Islamic Banks: Evidence from Islamic Banking in Southeast Asia - Pratiwi, Silvia Siska; Rahmi, Asri Noer; Yayuningsih, Siti; Palupi, Ade; Salsabila, Lilis (Jurnal Ekonomi Syariah Teori dan Terapan, 2024)
The aim of this research is to analyse the factors that influence the occurrence of non-performing financing in Islamic banks in Indonesia, Malaysia, the Philippines, and Brunei Darussalam. This research needs to be discussed because there was an increase in non-performing financing during the covid-19 pandemic. The design used in this study is a quantitative descriptive study with secondary data types. The sampling technique used is a purposive sampling technique with a population of Islamic banks in Indonesia, Malaysia, the Philippines, and Brunei Darussalam with a number of samples that meet the requirements of 26 Islamic banks. The data analysis method used is a parametric statistical method with multiple linear regression as a hypothesis testing method. This research uses SPSS Version 25 software to process the data. The results show that diversification, Capital Adequacy Ratio (CAR), Bank Size, Net Interest Margin (NIM), and Return on Asset (ROA) have a significant effect on non-performing financing. Meanwhile, the Financing to Deposits Ratio (FDR), Gross Domestic Product, and inflation have no significant effect on non-performing financing.